How Salty Are Your Fluids? Pediatric Maintenance IV Fluid Prescribing Practices Among Hospitalists - Hall, Alan M.; Ayus, Juan C.; Moritz, Michael L. (Frontiers in Pediatrics, 2020)
Objective: The primary goal of this study was to assess current maintenance intravenous fluid (mIVF) prescribing practices of pediatric hospitalists after the release of the American Academy of Pediatrics Clinical Practice Guideline (AAP CPG), specifically assessing the rates of various isotonic versus hypotonic solutions used in discrete age groups and in common clinical scenarios associated with anti-diuretic hormone (ADH) excess and hyponatremia. We hypothesized that isotonic fluids would be selected in most cases outside of the neonatal period. Methods: A voluntary and anonymous survey was distributed to the LISTSERV® for the AAP Section on Hospital Medicine. Results: There were 402 total responses (10.1% response rate) with the majority of respondents being pediatric hospitalists. Isotonic solutions were preferred by respondents in older children compared to younger age groups, at 87.8% for the 1-18 years age group compared to 66.3% for the 28 days to 1 year age group and 10.6% for the younger than 28 days age group (all p values <0.0001). When presented with disease states associated with ADH excess, isotonic fluids were preferred in higher percentages in all age groups except in children younger than 28 days when 0.45% sodium chloride was preferred; 0.2% sodium chloride was rarely chosen. Conclusions: Overall, based on survey responses, pediatric hospitalists are following the 2018 AAP CPG on mIVF and are more likely to choose isotonic fluids as their primary mIVF in pediatric patients outside of the neonatal period, including in scenarios of excess ADH. Isotonic fluids use seems to be higher with increasing age and hypotonic fluids continue to be more commonly chosen in the neonatal period.